Influence of hydric stress in the production of toxic principles in Nerium oleander L. - Pedrinho, D. R. (2010)
Many plants utilized in the urban center shows substances considered toxic whose production could be influenced by some factors, like hydric stress, including ornamental Nerium oleander L., widely used in gardens in various parts of the world, which presents production of cardioative glucosides, considered toxic. This study had the objective to evaluate the effect of field capacity in the biomass and the level of cardioative glucosides in seedlings of Nerium oleander. The experiment was carried at UNIDERP, in Campo Grande City, Mato Grosso do Sul State, Brazil, at the University for Development of State and Pantanal Region, using the experimental delineation in randomized blocks. There were 4 treatments (25%; 50%; 75% and 100% of the field capacity), 5 replications and 4 plants by parcel, totalling 80 plants. The evaluations were realized 60 days after the seedlings were planted. The quantitative analysis of the cardioative glucosides was realized by gravimetric test, after selective extraction of the glucosides. Were conclude that increase of the quantity of water in the soil raised the biomass production until 75% of the field capacity and increased the level of cardioative glucosides, showing that water management is very important and should be provided only the necessary to development of the plant.